Vertical and spatial differences in ozone formation sensitivities under different ozone pollution levels in eastern Chinese cities - Zhuang Wang; Hao Zhang; Chune Shi; Xianguang Ji; Yizhi Zhu; Congzi Xia; Xiaoyun Sun; Meng Zhang; Xinfeng Lin; Shaowei Yan; Yuan Zhou; Chengzhi Xing; et al. (npj Climate and Atmospheric Science)
Abstract Ozone is the primary air pollutant in eastern China during the warm season. Clarifying the differences in the spatio–temporal evolution of the ozone formation sensitivity between ozone polluted days and clean air days is key for the precise formulation of ozone prevention policies. By combining ground–and satellite–based remote sensing with ground station observations, we identified large spatio–temporal differences in the ozone formation sensitivity in eastern Chinese cities under different ozone pollution levels. Diurnally, the NO2 concentration was higher in the morning and lower at noon on the ozone exceedance days. The HCHO concentration was higher throughout the day, and the transition limited regime or NOx–limited regime contributed more to the ozone formation sensitivity on the ozone exceedance days. Vertically, the ratio of HCHO to NO2 (FNR) was higher on ozone exceedance days, and the contributions of NOx–limited regime at 0–2 km and the transition limited regime at 0–1 km on ozone exceedance days increased considerably. Spatially, HCHO in the North China Plain and middle–lower Yangtze River Plain was significantly increased on ozone exceedance days, while the NO2 concentration in the southeast hills was increased on ozone exceedance days. The difference in FNR values between northern and southern cities in eastern China on O3 exceedance days narrowed, and the ozone formation sensitivity in eastern China tended to be under a transition limited regime. The shifts in the ozone formation sensitivity under different ozone pollution levels implies that controlling only one of the precursors cannot achieve the best O3 prevention effect, and the most appropriate ratio of O3 precursor emission reductions should be designed according to ozone formation sensitivity in the different regions.